An Empirical Investigation of Third Party Logistics Providers in Thailand: Barriers, Motivation and Usage of Information Technologies - Kritchanchai, Duangpun; Tan, Albert Wee Kwan; Hosie, Peter (IGI Global, 2010)
Third Party Logistics (3PL) in Asia emerged as an important trend in logistical management and Thailand continues to develop in this service rapidly. While a great deal has been written about the dissemination of information technology (IT), few empirical investigations address the use of IT in relation to 3PLs in Thailand. In this article, the authors use an empirical study to investigate the profiles of 3PLs in Thailand and their company strategies for providing logistics service and use of IT. Survey results show that Thailand's 3PL companies must expend more effort to strengthen basic IT and infrastructure to enhance competitiveness. IT capabilities in Thailand are increasing rapidly and its effective adoption has the potential to significantly enhance the competitiveness of small 3PLs. Still many barriers exist to the successful adoption of IT by these providers. Given the importance of such companies in supply chain management, these issues must be fully understood.